1991
DOI: 10.1002/esp.3290160709
|View full text |Cite
|
Sign up to set email alerts
|

Summer and winter regimes of runoff generation and soil erosion on cultivated loess soils (The Netherlands)

Abstract: Monthly runoff and soil loss data of three fallow experimental plots are presented, comprising a summer and following winter season. The fallow plots were only tilled once, at the end of April. Summer runoff appeared to be controlled by rainfall intensity and conforms to the Horton model of overland flow generation. Winter runoff was primarily controlled by rainfall amount and conforms to the saturation or storage control model of runoff generation. Summer runoff volume was one fourth of winter runoff volume. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 17 publications
2
32
0
1
Order By: Relevance
“…The process held responsible for this is liquefaction of aggregates in a very wet state at soil moisture contents exceeding the liquid limit of the soil. This may have occurred under the influence of a temporary high (perched) water table, which was observed on the experimental plots in the winter half of the year (Kwaad, 1991). Evidently, the bulk of the tilled layer has lost its granular structure in one of two ways: (a) by a gradual welding of aggregates in a non-saturated state over a period of some months, or (b) by a collapse of aggregates and inter-aggregate pores when the soil was saturated.…”
Section: Microscopic Analysis Of Soil Thin Sectionsmentioning
confidence: 97%
“…The process held responsible for this is liquefaction of aggregates in a very wet state at soil moisture contents exceeding the liquid limit of the soil. This may have occurred under the influence of a temporary high (perched) water table, which was observed on the experimental plots in the winter half of the year (Kwaad, 1991). Evidently, the bulk of the tilled layer has lost its granular structure in one of two ways: (a) by a gradual welding of aggregates in a non-saturated state over a period of some months, or (b) by a collapse of aggregates and inter-aggregate pores when the soil was saturated.…”
Section: Microscopic Analysis Of Soil Thin Sectionsmentioning
confidence: 97%
“…They mentioned an average amount of 6.7 t ha À1 of displaced soil in rills and gullies during the winter of 1983-84 in 18 first-order catchments in a 1060-ha area (Ransdalerveld) where re-allotment of land had recently been carried out, and 3-30 t ha À1 of displaced soil in 6 months on some 30 arable field sites throughout South-Limbourg. The most recent data on the rate of erosion under row crops were collected during an experimental plot study from 1986 to 1993 (Kwaad, 1991;Kwaad et al, 1998). Sediment output on a catchment level was measured during a field project from 1991 to 1994 (De Roo et al, 1995;Van Dijk and Kwaad, 1994b;Van Dijk, 2001).…”
Section: Erosion and Conservation Research In South-limbourgmentioning
confidence: 99%
“…In the course of the work, however, overland flow was also observed under conditions of low-intensity rainfall. Using various types of evidence, Kwaad (1991Kwaad ( , 1993Kwaad ( , 1998 and Van Dijk and Kwaad (1996) convincingly showed the occurrence of saturation overland flow in the region. In Table 1.31.3 some results on a storm by storm basis in the St. Gillistraat-2 catchment (4.8 ha) are given.…”
mentioning
confidence: 96%
“…It has been shown, however, that erosion from saturation excess overland flow in the winter Ž . during mild rains can be significant Kwaad, 1991 . It has also been shown that topographic convergence and subsurface processes are related to erosion due to the Ž formation of ephemeral or thalweg gullies.…”
Section: Water Fluxes and Runoff Generating Processesmentioning
confidence: 99%